2011
DOI: 10.1088/0029-5515/51/8/083032
|View full text |Cite
|
Sign up to set email alerts
|

Lower hybrid current drive at high density in Alcator C-Mod

Abstract: Abstract. Experimental observations of lower hybrid current drive (LHCD) at high density on the Alcator C-Mod tokamak are presented in this paper. Bremsstrahlung emission from relativistic fast electrons in the core plasma drops suddenly above line averaged densities of 10 20 m −3 (ω/ω LH ∼ 3) in single null discharges with large (> 10 mm) plasma-inner wall gaps, well below the density limit previously observed on limited tokamaks (ω/ω LH ∼ 2). Modeling and experimental evidence suggest that the absence of LHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 25 publications
6
57
1
Order By: Relevance
“…Above the frequency spectrum is eventually dominated by PDI at the outer wall side, similar to what was observed in single null plasmas. However, its strength as measured with the inner-wall probe is somewhat weaker than that observed in Figure 4, and this correlates with the previous observation of a higher hard X-ray count rates in double null plasmas than in single null plasmas [15]. Nonetheless, one needs to be careful when predicting PDI effects with inside launch based only on this result because both the plasma condition and wave propagation would not be same as what they would be with inside launch.…”
Section: Implications For Future Lhcd Experimentssupporting
confidence: 60%
“…Above the frequency spectrum is eventually dominated by PDI at the outer wall side, similar to what was observed in single null plasmas. However, its strength as measured with the inner-wall probe is somewhat weaker than that observed in Figure 4, and this correlates with the previous observation of a higher hard X-ray count rates in double null plasmas than in single null plasmas [15]. Nonetheless, one needs to be careful when predicting PDI effects with inside launch based only on this result because both the plasma condition and wave propagation would not be same as what they would be with inside launch.…”
Section: Implications For Future Lhcd Experimentssupporting
confidence: 60%
“…Previously, we reported that the LHCD performance recovered by using a limited magnetic configuration in Ref. [13]. An alternate approach to recover the current drive in a diverted configuration was discovered last year when we measured the dependency of CD efficiency in a wide range of plasma current [14].…”
Section: Experimental Progresses To Improve Lhcd At High Densitymentioning
confidence: 99%
“…A helical internal kink-like mode [7][8][9] with dominant poloidal and toroidal mode numbers m = 1, n = 1 has recently been observed in the Alcator C-Mod tokamak 10 , during the development of advanced fusion scenarios using lower hybrid current drive (LHCD) [11][12][13] . During LHCD operation, soft x-ray (SXR) detectors measure periodic bursts of oscillations as shown in Fig.…”
mentioning
confidence: 99%
“…is the Lorentz factor 13,[20][21][22][23] . Electron cyclotron waves emitted in the core at these frequencies can travel to the outboard plasma edge without being re-absorbed by the thermal electrons.…”
mentioning
confidence: 99%